Contribution of Reaction Speed ​​and Arm Muscle Strength to Backhand Punch Ability in Tennis - Syakad Al Fakhi; Eri Barlian (Performa, 2019)
This study aims to see how much the contribution of reaction speed and arm muscle strength to the backhand ability of students at the Faculty of Sport Science, Padang State University.This research method is correlation. The population in this study were students who took part in the tennis court classes and only 20 male students were sampled, using a purposive sampling technique. This research was conducted on September 24, 2019, taking place in the indoor tennis court of the Faculty of Sport Science, Padang State University. Reaction velocity data were taken with the whole body reaction test, arm muscle strength with a two hand medicine ball put test, and the ability to test the ability of backhand tennis court. The data analysis technique of this study used the requirements analysis test technique, namely the normality test and continued with product moment correlation analysis, multiple correlation then continued with the regression test.The results of data analysis show that: (1). There is a contribution between reaction speed and backhand capability, which is 16%; (2) there is a contribution between the strength of the arm muscles towards the ability to backhand, which is 30%; (3) there is a contribution between reaction speed and arm muscle strength together to the backhand ability, which is 36%.